Evaluation of sodium butyrate and nutrient concentration for broiler chickens - J.J. Mallo (Elsevier, 2021)
ABSTRACT: The relation between nutrition and intestinal health is a subject with an increasing interest in research, as nutritionists need knowledge about how formulation affects different parameters in the gastrointestinal tract (GIT). That is why 4 trials were conducted to evaluate the effect of nutrient concentration and a feed additive (sodium butyrate protected with sodium salts of palm fatty acid distillates (PSB, Gustor N'RGY produced by Norel S.A., Spain, dosed at 1 kg/t), on performance, diet digestibility, intestinal morphology, volatile fatty acid concentration (VFA) in the GIT and intestinal microbiota of broiler chickens, when fed diets with different energy and amino acids concentration. Control diets, C, with the recommended metabolizable energy (ME) and ideal amino acid (AA) composition; Reduction 1, R1, C – 60 kcal ME and – 2.3% AA and Reduction 2, R2, C – 120 kcal ME and – 4.6% AA) based on different feed ingredients (Corn Soy [CS] and Wheat Barley Soy (WBS) were formulated. All trials lasted 42 d. In trials 2 and 4, the nutrient dilution decreased performance of the animals. In all trials, PSB improved animal performance (growth or FCR), despite the different situations. In trials 1 and 4, animals receiving R1 diets and PSB showed similar performance to those receiving C diets without PSB. PSB improved Gross Energy metabolizability (69.94 vs. 72.55; P: 0.02). Nutrient concentration affected histology results in T2 (ileum) and T3 (jejunum); PSB showed effects in T2 (jejunum, ileum) and in T3 (jejunum). In T1, PSB affected VFA in duodenum, jejunum, and ileum, changing the profile depending on diet nutrient concentration. PSB altered microbiology in caecum of animals in T2. It can be concluded that the dilution of ME and AA concentration of the diet impairs animal performance, influences intestinal microbiota and affects intestinal histology. PSB improves animal performance, increases gross energy metabolizability, steers intestinal microbiota and alters VFA concentrations in the intestine. The addition of PSB may help the animal to counteract the negative effects of diluted diets.